Sustainability Reporting Analysis at PT Minna Padi Investama Sekuritas TBK Based on the Perspective of Scientific Literature and Sustainable Finance Regulations in Indonesia - Ni Komang Ari Krisnawati (International Journal of Environmental, Sustainability, and Social Science (IJESSS), 2026)
This study analyzes the 2024 Sustainability Report of PT Minna Padi Investama Sekuritas Tbk with reference to POJK No. 51/POJK.03/2017 and the Global Reporting Initiative (GRI Standards 2021). Using a qualitative descriptive literature review method, data were obtained through content analysis of company reports and literature related to Environmental, Social, and Governance (ESG) practices in the non-banking financial services sector. The results show that the report structure complies with OJK regulations, but the quality of disclosure is still limited. Economic aspects are reported transparently but are not yet linked to sustainability initiatives, social aspects focus on internal employees without community involvement, and environmental aspects only list energy consumption without performance indicators. The governance aspect shows a commitment through ISO 27001 certification, but does not yet have a sustainability committee or independent verification. Overall, Minna Padi's sustainability reporting maturity level is at the developing stage.